Integrating CALL Into English Language Learning: Bangladeshi College Students’ Perceptions and Challenges - Ashim Kumar Paul (Journal of English Education and Teaching, 2020)
This study aims to explore Bangladeshi college students’ attitude, perception, interests and challenges with regard to the application of Computer Assisted Language Learning (CALL) in learning English. A mixed method research was designed and administered to obtain the purposes of the present study. One hundred undergraduate students (52 male and 48 female) of English Department studying at a government college in Bangladesh participated in the questionnaire survey while twenty students (11 male and 09 female) were purposively chosen for the semi-structured interview section. The collected data of quantitative part were analysed by SPSS software and the responses of the qualitative part were thematically analysed. The findings revealed that students showed positive attitude towards the integration of CALL in English language learning and teaching process. Nonetheless, the Chi-square value revealed that there is no significant relationship between gender variation and the attitude to CALL. The results also revealed that students face some difficulties in using computer and other relevant technological equipment for English Language learning. The results provide concepts and suggestions to the future researchers for further investigations in relation to CALL for the benefits of learners and learning.